Distinction, Trajectory, Aromatherapy as Capital Distribution on AgroTourism Destinations Bukit Waruwangi, Serang-Banten - Fitria Angeliqa; Ucca Widya Satyanti; Zalfadianti Khairunnisa Achmad (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2022)
Agrotourism and ecotourism immediately became a trend when the Covid-19 pandemic began to increase and social activity restrictions took effect. This particular market requires the foresight of tourism actors and local governments to provide an open interaction space for residents. This article aims to explain how the postmodern approach with its vision of empowerment is used in agro-tourism destination brands by finding typical behavior in its operations. Using the capital and distinction terminology of Pierre Bourdieu, this study uses a mixed-method approach in the form of network analysis in social media (Youtube, Instagram, and online media coverage) to obtain quantitative data. At the same time, in-depth interviews and observation explored qualitative data. The results show that data on all social media platforms showed positive sentiment. Meanwhile, the results of in-depth interviews show how visitors are willing to take the difficult path to get the essential experiences conveyed in their social media accounts. Data observations also provide an overview of herbal plants cultivation as a way of land use and reflect the habits of residents involved in this agrotourism operation. Thus, the location is the cultural capital, while the natural scenery is Bukit Waruwangi (BWW) symbolic capital as an agro-tourism destination. The voluntary testimonials of visitors in social media accounts are proof of BWW's extensive and networked social capital. While cultivating aromatherapy as a natural product beneficial for health, it is BWW's distinction to differentiate itself in the competitive arena. Aromatherapy and essential oil products are the trajectories of plants that are closely related to palliative medicine in the context of Indonesian culture.